2020
DOI: 10.3390/nu12082487
|View full text |Cite
|
Sign up to set email alerts
|

A Paradoxical Vasodilatory Nutraceutical Intervention for Prevention and Attenuation of Migraine—A Hypothetical Review

Abstract: Studies suggest that migraine pain has a vascular component. The prevailing dogma is that peripheral vasoconstriction activates baroreceptors in central, large arteries. Dilatation of central vessels stimulates nociceptors and induces cortical spreading depression. Studies investigating nitric oxide (NO) donors support the indicated hypothesis that pain is amplified when acutely administered. In this review, we provide an alternate hypothesis which, if substantiated, may provide therapeutic opportunities for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Rather, it has been proposed that with dilation of the great arteries, there is vasoconstriction downstream of the cerebral microcirculation, raising the notion of an alternative causation. 17,22 One of the major determinants of cerebral blood flow is blood viscosity, and studies have shown that cerebral blood flow regulation has a dominant role in primary headaches such as migraine. [23][24][25][26] Whole blood is a non-newtonian fluid, which means that the viscosity of the blood depends on the shear rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it has been proposed that with dilation of the great arteries, there is vasoconstriction downstream of the cerebral microcirculation, raising the notion of an alternative causation. 17,22 One of the major determinants of cerebral blood flow is blood viscosity, and studies have shown that cerebral blood flow regulation has a dominant role in primary headaches such as migraine. [23][24][25][26] Whole blood is a non-newtonian fluid, which means that the viscosity of the blood depends on the shear rate.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In our study, we found more NIH development in those with high WBV. This effect may be due to reflex vasoconstriction in the microvascular bed as a result of vasodilation of the large cerebral arteries, 17,22 further accentuating the effect of blood viscosity, which is of critical importance for blood flow. Because nitrates cause reflex vasoconstriction at the microvascular level, impair tissue perfusion, and stimulate nociceptors, we can say that blood viscosity, which has a stable hemorheological status under normal conditions, differentiates its hemorheological properties after nitrate use and shows a significant interaction in blood flow mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…In CSF, pathway enrichment analysis identified arginine/proline metabolism and glutamate/glutamine metabolism as associated to one clinical symptom (MD worst eye). Arginine metabolism has previously been linked to the development and treatment of migraines through its role in the synthesis of nitric oxide. Nitric oxide is synthesized from arginine by the endothelial nitric oxide synthase and synthesizes citrulline as a byproduct. , Nitric oxide is important in smooth muscle relaxation, vasodilation, and increased blood flow and is a potent headache provocation agent . It is possible that the perturbed arginine metabolism with downstream effects on nitric oxide may be linked to the severe headache phenotype in IIH .…”
Section: Discussionmentioning
confidence: 99%
“…Now, there is an enlarged use of natural products as an antioxidant instead of synthetic chemicals [46]. In this respective, the alleviation efficacy of garlic may be due to its antioxidant properties as the garlic can scavenge reactive oxygen species [47], specifically superoxide radicals [48], and neutralize hydrogen peroxide, by causing the increase in the activity of SOD, CAT, and GPx, leading to prevention of hydrogen peroxide-induced cell damage [49]. Garlic also can obstruct lipid peroxidation by scavenging the hydroxyl and peroxyl radicals [50].…”
Section: Discussionmentioning
confidence: 99%